Thermal comfort in naturally ventilated buildings of Maracaibo, Venezuela - Bravo Morales, Gaudy Claret; González Cruz, Eduardo Manuel (Rev. Téc. Fac. Ing. Univ. Zulia)
This document presents an evaluation of air temperatures and human thermal votes registered on three constructive typology naturally ventilated buildings located in Maracaibo, Venezuela. The results show differences in the indoor air temperatures, the thermal votes and in the indoor comfort temperatures estimates by building typology.